Engineering carboxymethylproline synthases towards the biosynthetic productions of carbapenem antibiotics - Gómez Castellanos, J (2013)
Mechanistic and biocatalytic studies of two carboxymethylproline synthases (CMPSs), CarB and ThnE, members of the crotonase superfamily of enzymes, both in isolation and in conjunction with the activity of the crotonyl-CoA carboxylase/reductase (Ccr) the malonyl-CoA synthetase (MatB) and the methylmalonyl-CoA epimerase (MCE) are presented. Protein engineering studies on carboxymethylproline synthases aimed at enabling stereoselective C–C bond formation leading to N-heterocycles via control of trisubstituted enolate intermediates were carried out. Active site substitutions, including at the oxyanion binding site, enabled the production of substituted N-heterocycles in high diastereomeric excesses via stereocontrolled enolate formation and reaction. The biocatalytic promiscuity of malonyl-CoA ligase and the stereoselectivity of crotonyl–CoA carboxylase/reductase were successfully coupled to the selective tri- substituted enolate forming capacity of engineered carboxymethylproline synthases for the preparation of functionalized 5- and 6-membered N-heterocycles substituted with a variety of alkyl side chains at the C-5/C-6 positions at high diastereomeric excess. The effect of methylmalonyl-CoA epimerase on the diastereoselectivity of the carboxymethylproline synthase-catalysed enolated alkylation was also demonstrated. The results illustrate the utility of the crotonase superfamily of enzymes for stereoselective biocatalysis and demonstrate the power of coupled enzyme systems to enhance diastereoselectivity and to expand the range of accepted substrates.